Impact of variants of MMP‐7(‐181A>G) gene in susceptibility to the development of HIV‐associated neurocognitive disorder and its severity. Issue 11 (19th August 2016) - Singh, HariOm; Marathe, Shruti D.; Nain, Sumitra; Nema, Vijay; Angadi, Mansa; Bapat, Shradha S.; Ghate, Manisha V.; Gangakhedkar, Raman R.
Abstract : The HIV‐1‐induced neurological toxicity has been associated with the deficiency of matrix metalloproteinases. Tat protein of HIV up regulates MMP‐7 release and activation, leading to neurotoxicity. The SNP ‐181A>G of MMP‐7 is known to have functional effects on its promoter activity. Therefore, we aimed to evaluate the association of variants of MMP‐7 ‐181A>G gene in HIV‐associated neurocognitive disorder (HAND). In the present case–control study, we recruited 50 HIV‐infected individuals with HAND, 130 HIV‐infected individuals without HAND and 150 unrelated healthy individuals. Polymorphism for MMP‐7 ‐181A>G gene was genotyped by PCR‐RFLP method. Frequency of ‐181GG and G allele of MMP‐7 did not differ significantly between patients with HAND and without HAND (8.0% vs 13.1%, p = 0.22 and 31% vs 38.1%, p = 0.21). Individuals with ‐181 AG, ‐181GG genotype, and G allele of MMP‐7 were found to have reduced the risk of development of HAND but not significant (50.0% vs 51.9%, p = 0.09, OR = 0.54; 13.1% vs 19.0%, p = 0.33, OR = 0.71 and 38.1% vs 44.9%, p = 0.09, OR = 0.75). Individuals in early HIV disease stage having ‐181AG genotype and ‐181AG + GG combined genotype of MMP‐7 were not associated with the development of HAND (OR = 1.27, p = 0.25 and OR = 1.25, p = 0.17). Tobacco and alcohol consumption among individuals with any genotype of MMP‐7 was not associated with the risk of development of HAND. In conclusion, individuals with ‐181GG genotype and G allele had no impact on susceptibility to the development of HAND and its severity.